Exploring bioflavonoids as novel antivirals against Chikungunya virus / Rafidah Lani - Rafidah, Lani (2016)
Chikungunya virus (CHIKV) is a mosquito-borne virus that recently has been classified as a Category C pathogen by National Institute of Allergy and Infectious Diseases (NIAID). This alphavirus causes several clinical features similar to dengue virus infection, except polyarthritis and tenosynovitis, where the similarities would usually cause misdiagnosis. CHIKV has caused many large outbreaks all over sub-Sahara Africa and tropical Asia including India and the Western Pacific. This could possibly turn into an emerging global pandemic if no effective preventive measures are taken. Since CHIKV spreads by increased global travels, immunologically naive populations such as in the United States (US) is at risk, since it is one of the non-endemic regions. Besides the US recently, there have been travel-associated CHIKV cases in Australia, Asia and European countries as well. The challenge posed by CHIKV is there is no vaccine and antiviral treatment currently available for CHIKV infection. CHIKV infection is treated symptomatically by the administration of non-steroidal anti-inflammatory drugs or steroids, bed rest and fluids. In worst case scenarios, such as debilitating chronic CHIKV infection, corticosteroids is the only option. Available treatments such as chloroquine can only inhibit CHIKV cell-to-cell spread but not the replication of the infected cells. Research on vaccines and antivirals are still actively pursued to produce safer vaccines with longer protective effects and persistent antibodies. Live vaccines were produced, but with side effects including risks of producing chronic rheumatism. Most antiviral drugs that have been suggested are nucleoside analogues where they are potentially teratogenic, embryotoxic, carcinogenic and possess anti-proliferative activities. iv Turning to organic sources may prove to be more beneficial in the search for anti-CHIKV compounds, such as natural bioflavonoids which can be derived from most herbal medicines and ordinary fruits. Bioflavonoids are phenolic compounds that possess anti-oxidant, anti-tumor, anti-proliferative, anti-inflammatory, antibacterial and antiviral activities. Thus, in this study, the main objective is to find non-toxic bioflavonoid compounds that could inhibit the CHIKV infection or at least reduce the CHIKV replication at in vitro level. In order to meet the objectives of this study, various antiviral assays were performed including the CHIKV replicon cell line-based assay, immunofluorescence assay and western blotting analyses. The replication efficiency of CHIKV at each antiviral assay was determined by using the qRT-PCR assay with RNA copy number as the parameter. Statistical analysis was performed by using the Graph Pad Prism 5 software with suitable statistical analysis for each assay. Through this study, 4 out of 14 bioflavonoid compounds were identified to exhibit intracellular antiviral activity against CHIKV at different stages of CHIKV life cycle. These compounds are baicalein, fisetin, quercetagetin and silymarin. These compounds were also able to suppress the accumulation of important CHIKV proteins such as pE2, E2, nsP1 and nsP3 proteins in addition to the ability to interfere with CHIKV replication cycle. This study is the first step towards finding a potent anti-CHIKV compound.